2020
DOI: 10.3390/nu12092683
|View full text |Cite
|
Sign up to set email alerts
|

Traits of Orthorexia Nervosa and the Determinants of These Behaviors in Elite Athletes

Abstract: Background: The purpose of this study was to evaluate the traits of orthorexia nervosa (ON) and its relation to body composition and anthropometric indices among elite athletes. Methods: We studied 273 (125 female, 148 male) competitive athletes. ON was assessed with the self-administered ORTO-15 questionnaire. Total body composition was determined using dual-energy X-ray absorptiometry (DXA). Results: The ORTO-15 score was independent of sex, type of effort or age. The ORTO-15 score was related to: total body… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 49 publications
3
26
0
Order By: Relevance
“…The data obtained from this survey, albeit preliminary, allow us to con irm the discrepancy between the real body image and the desired one in a group of athletes who, with the advancement of age and/or competitiveness, favors the adoption of certainly not adaptive strategies to control weight. These indings accord with many studies present in literature that have found a link between sports activity and the onset of EDs [20][21][22][23][24][25][26][27][28].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The data obtained from this survey, albeit preliminary, allow us to con irm the discrepancy between the real body image and the desired one in a group of athletes who, with the advancement of age and/or competitiveness, favors the adoption of certainly not adaptive strategies to control weight. These indings accord with many studies present in literature that have found a link between sports activity and the onset of EDs [20][21][22][23][24][25][26][27][28].…”
Section: Discussionsupporting
confidence: 92%
“…Many studies have found a close link between sports activity and the onset of EDs and agree that EDs are more common in female athletes than in non-athletes [20][21][22][23][24][25][26][27][28]. Lots of scienti ic papers address this complex issue.…”
Section: Body Image and Eating Disordersmentioning
confidence: 99%
See 3 more Smart Citations